Legal authority in premodern Islam : Yahya b. Sharaf al-Nawawi in the Shafi'i school of law - Halim, Fachrizal A. (Milton Park, Abingdon, Oxon : Routledge, 2015)
'This book presents a comprehensive picture of the structure of authority in Islamic law. It does this specifically within the Shafi'ite legal tradition and the novel aspects of al-Nawawi's legacy and contributions'--
'Offering a detailed analysis of the structure of authority in Islamic law, this book focuses on the figure of Yahya Sharaf al-Nawawi who is regarded as the chief contributor to the legal tradition known as the Shafi'i madhhab in traditional Muslim sources, named after Muhammad b. Idris al-Shafi'i d. 204/820), the supposed founder of the school of law. Al-Nawawi's legal authority is situated in a context where Muslims demanded to stabilize legal disposition that is consistent with the authority of the madhhab, since in premodern Islamic society, the ruling powers did not produce or promulgate law, as was the case in other, monarchic civilizations. Al-Nawawi's place in the long-term formation of the madhhab is significant for many reasons but for one in particular: his effort in reconciling the two major interpretive communities among the Shafiiites, i.e., the tariqas of the Iraqians and Khurasanians. This book revisits the history of the Shafi'i school in the pre-Nawawic era and explores its later development in the post-Nawawic period. Presenting a comprehensive picture of the structure of authority in Islamic law, specifically within the Shafi'ite legal tradition, this book is an essential resource for students and scholars of Islamic Studies, History and Law'--
Introduction -- The man and his biography -- The reception and routinization of his legacy -- Two communities of interpretation : Tariqa of the Iraqians and the Khurassanians -- The cononization of the school's doctrines -- Al-Nawawi's definition and vindication of the madhhab.
Includes bibliographical references and index.
Keywords: al-Nawawi, -- 1233-1277.; Islamic law -- Interpretation and construction; Shafiites